PENINGKATAN PENGAMALAN NILAI KEISLAMAN DI DESA SEMUDUN KABUPATEN MEMPAWAH - Samsuddin Samsuddin; Ahmad Husein (Universitas Muhammadiyah Pontianak, 2016)
Semudun village is one of the villages in Sungai Kunyit with an area of 780 hectares. At first, Semudun village was united with Mendalok village. Along with the development of villages and population growth, Semudun village was divided into Mendalok village, located in the North side and Semudun Village in the south part. Based on problems and potentials of Semudun village above, and also consideration of expertise knowledge, the activities of community services which will be held in the village Semudun just at the aspect of lacking of syiar Islam and low incomes. To address both of these problems, associated with its potential, activities was focused increased activity in the mosque in the form of pengajian and establishment AlQuran Education Centre in the mosque. Meanwhile, to increase people's income was associated with the potential of fish resources to be carried in explanation and training of manufacturing of processed fish products after harvest, so the fish were obtained not only sold directly in the market, but were processed further do increase the economic value of fish that will impact on rising incomes. Keywords: semudun village Problems, semudun village potential, increased Syiar, improve household incomes.